Effects of Puerarin on Lipid Accumulation and Metabolism in High-Fat Diet-Fed Mice - Zheng, Guodong (PLoS One, 2015)
In order to investigate the mechanisms by which puerarin from kudzu root extract regulates lipid metabolism, fifty mice were randomly assigned to five groups: normal diet, high-fat diet (HFD), and HFD containing 0.2%, 0.4% or 0.8% puerarin for 12 weeks. Body weight, intraperitioneal adipose tissue (IPAT) weight, serum biochemical parameters, and hepatic and feces lipids were measured. Activity and mRNA and protein expressions of hepatic lipid metabolism-related enzymes were analyzed. Compared with HFD, 0.4% and 0.8% puerarin significantly decreased body and IPAT weight. There was a significant decrease in the serum and hepatic concentrations of total cholesterol, triglycerides and leptin in mice fed the 0.4% and 0.8% puerarin diets compared with HFD. Fatty acid synthase activity was suppressed in mice fed the 0.4% and 0.8% puerarin diets, while the activities of AMP-activated protein kinase (AMPK), carnitine acyltransferase (CAT) and hormone-sensitive lipase (HSL) were increased. mRNA expression of peroxisome proliferator-activated receptor γ 2 (PPARγ 2) was down-regulated in liver of mice fed the 0.8% diet compared with HFD, while mRNA expression of CAT and HSL was considerably up-regulated by 0.4% and 0.8% puerarin diets. The protein expression of PPARγ2 in liver was decreased and those of p-AMPK, HSL and p-HSL were increased in mice fed 0.4% and 0.8% puerarin diets. These results suggest that > 0.4% puerarin influenced the activity, mRNA and protein levels of hepatic lipid metabolism-related enzymes, decreasing serum and liver lipids, body weight gain and fat accumulation. Puerarin might be beneficial to prevent lifestyle-related diseases.